The role of educational sports information in modifying the attitudes of middle school students towards physical and sports activities. - Experimental study on a sample of Bedjaoui ELArbi middle school in Biskra - brahimi issa; salhaoui hasnaa (sports creativity, 2025)
The objective of this study is to try to developed a media sportive educational visualization In order to modify students' attitudes towards physical and sports activities. Depending on a background theory. We designed a school sports media program Consists of 21 pages. We used the experimental method to apply the program to 15 students. We used for pre and after measurement Kenyon scale for physical and sports activities attitudes . the most important results obtained : The proposed sports media program has a role in modifying the attitudes of middle school students toward physical and sports activities